Pengaruh Aktivitas Fisik Terhadap Kecepatan Waktu Reaksi pada Unit Kegiatan Mahasiswa Futsal UKRIDA 2023 - Yazmin, Aneta Almira; Rumiati, Flora; Evan, Evan (Universitas Kristen Krida Wacana, 2025)
Reaction time is the duration between an individual receiving a stimulus and the formation of a motor response to that stimulus. One effective method to enhance reaction time is through regular physical activity. Exercise has the potential to increase blood and oxygen flow to skeletal muscles and the brain which can affect a person's reaction time. This study aims to determine the average reaction time before and after physical activity and explore the influence of reaction time on the amount of exercise among respondents. The research adopts a quantitative experimental approach with a one-group pre and post-test design. The total sampling method involves 36 respondents who meet inclusion and exclusion criteria. The findings, analyzed using the Wilcoxon test with p=0.00 (p>0.05), indicate a significant impact of physical activity on the reaction time speed in the student futsal unit of the Faculty of Medicine at Kristen Krida Wacana University in 2023. This research serves as a reference for the community, highlighting the importance of regular physical exercise to improve reaction time. A faster reaction time enables individuals to respond more efficiently and make accurate decisions in a short period during various activities.